A kind of brown plant ash glaze and preparation method thereof

By adding spinel-garnet-type red-brown composite pigments and composite crystals to the wood ash glaze, the problems of single color and insufficient strength of the traditional wood ash glaze are solved, and the glaze color diversification and performance improvement are achieved.

CN118420227BActive Publication Date: 2025-04-04CHINA ACAD OF ART +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410668609.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-04-04
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

Traditional wood ash glaze has a single color, and due to its amorphous structure, poor strength and easy cracking, it is difficult to meet the market's demand for diversified glaze colors and high durability.

Method used

Add spinel-garnet-type reddish-brown composite pigment on the basis of wood ash and clay to adjust the color of the glaze, and improve the thermal expansion performance and strength of the glaze through spinel-garnet composite crystals.

Benefits of technology

The glaze color has been diversified, the thermal expansion performance and strength of the wood ash glaze has been significantly improved, cracked, and the application range of ceramic products has been expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004861942650000101
    Figure BDA0004861942650000101
Patent Text Reader

Abstract

The invention discloses a sauce-colored plant ash glaze and a preparation method thereof, which comprises the following raw materials by weight: 55-65 parts of plant ash, 30-40 parts of clay, and 3-8 parts of spinel-garnet type red-brown composite pigment; the spinel-garnet type red-brown composite pigment is made by co-firing 90-100 parts of FeCrZn spinel pigment, 13-15 parts of Y2O3, and 12-14 parts of Al2O3; the raw materials of the FeCrZn spinel pigment include by weight: 25-35 parts of Fe2O3, 15-20 parts of Cr2O3, and 35-55 parts of ZnO. The invention adds a spinel-garnet type red-brown composite pigment on the basis of plant ash and clay, and the color of the plant ash glaze can be adjusted to a sauce color, meeting the market demand for diversified glaze colors; and the thermal expansion performance and strength of the plant ash glaze are significantly improved, and the cracking thereof is prevented, thereby expanding the application of plant ash glaze ceramic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic glazes, in particular to a brown plant ash glaze and a preparation method thereof. Background Art

[0002] Plant ash glaze is a traditional ceramic glaze made of plant ash as the main raw material. Plant ash plays a major role in promoting melting and improving glaze effects in ceramic glazes. First, as a calcium carbonate salt, plant ash can be used as an aggregate to reduce the melting point and viscosity of the glaze and promote the melting of the glaze; secondly, plant ash can make the glaze surface smoother, more delicate, and more lustrous, improving the beauty of the glaze. Plant ash is an indispensable raw material for high-temperature glazes in China throughout the ages, so there is an old saying that "no ash, no glaze."

[0003] Traditional wood ash glazes are mostly green in color, which is mainly determined by the chemical composition of the wood ash and the firing process. However, a single color can no longer meet the market's growing demand for a variety of glaze colors. In addition, wood ash glaze is a non-crystalline glaze, and its crystals are not dense enough, so it has poor strength and is easy to crack. It is not suitable for products that require high durability and sealing, such as tableware. Summary of the invention

[0004] The present invention aims to overcome the above-mentioned problems existing in the wood ash glaze in the prior art, and provides a brown wood ash glaze and a preparation method thereof. A spinel-garnet type red-brown composite pigment is added to wood ash and clay, so that the color of the wood ash glaze can be adjusted to a brown color, meeting the market demand for diversified glaze colors; and significantly improving the thermal expansion properties and strength of the wood ash glaze, preventing it from cracking, and expanding the application of wood ash glaze ceramic products.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A brown wood ash glaze comprises the following raw materials, measured by weight: 55 to 65 parts of wood ash, 30 to 40 parts of clay, and 3 to 8 parts of spinel-garnet type reddish brown composite pigment;

[0007] The spinel-garnet type reddish brown composite pigment is prepared by co-firing 90-100 parts of FeCrZn spinel pigment, 13-15 parts of Y2O3 and 12-14 parts of Al2O3; the raw materials of the FeCrZn spinel pigment include, by weight: 25-35 parts of Fe2O3, 15-20 parts of Cr2O3 and 35-55 parts of ZnO.

[0008] The present invention adds an appropriate amount of spinel-garnet type reddish brown composite pigment to the traditional wood ash glaze components wood ash and clay, so that the color of the wood ash glaze can be adjusted from traditional blue-green to brown, meeting the market demand for diversified glaze colors. In addition, the addition of spinel-garnet composite crystals can significantly improve the thermal expansion properties and strength of the amorphous wood ash glaze, prevent it from cracking, and expand the application of wood ash glaze ceramic products.

[0009] In the composite pigment of the present invention, the FeCrZn spinel pigment is reddish brown, and the yttrium aluminum garnet formed after co-firing with Y2O3 and Al2O3 will not affect its color, and the composite of yttrium aluminum garnet can further improve the pigment's improvement of the glaze's anti-cracking performance. At the same time, when the FeCrZn spinel pigment is co-fired with Al2O3, part of the Al2O3 will be solid-dissolved in the spinel lattice, which is also beneficial to improving the glaze's anti-cracking performance.

[0010] Preferably, the clay comprises, by mass percentage, 0.05-0.07% Na2O, 0.1-0.2% MgO, 18-19% Al2O3, 74-76% SiO2, 3-4% K2O, 0.1-0.2% CaO, 0.08-0.12% TiO2, 0.7-0.9% Fe2O3, and the remainder is loss on ignition.

[0011] The present invention also discloses a method for preparing the above-mentioned brown plant ash glaze, comprising the following steps:

[0012] (1) Pretreatment of wood ash and clay;

[0013] (2) Preparing a spinel-garnet type reddish brown composite pigment: Fe2O3, Cr2O3 and ZnO are mixed in proportion, pressed into shape, sintered and crushed to obtain a FeCrZn spinel pigment; then the FeCrZn spinel pigment is mixed with Y2O3 and Al2O3 in proportion, pressed into shape, sintered and crushed to obtain a spinel-garnet type reddish brown composite pigment;

[0014] (3) Mixing and ball milling: the pre-treated plant ash and clay are mixed with the spinel-garnet type red-brown composite pigment in proportion, and then the mixture is ball milled with water. After ball milling, the mixture is sieved to obtain a glaze;

[0015] (4) Glazing: placing the fired ceramic body into the glaze;

[0016] (5) Drying: Drying the ceramic body after glazing;

[0017] (6) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface.

[0018] Preferably, during the pretreatment in step (1), the plant ash is passed through an 80-120 mesh sieve to remove impurities, then soaked in water for precipitation, the water is poured out after precipitation, new water is added, the precipitation is repeated 3-5 times, the water is poured out, and the pretreated plant ash is obtained after drying; when the clay is pretreated, the clay is crushed and passed through a 100-120 mesh sieve to remove impurities, thereby obtaining the pretreated clay.

[0019] Preferably, when preparing FeCrZn spinel pigment in step (2), the sintering temperature is 1300-1400°C, and the sintering time is 3-5 hours; when preparing spinel-garnet type reddish brown composite pigment, the sintering temperature is 1700-1750°C, and the sintering time is 3-4 hours.

[0020] Preferably, when preparing the FeCrZn spinel pigment and the spinel-garnet type reddish brown composite pigment in step (2), the pressed green body is dried at 100-120° C. for 12-24 h before sintering.

[0021] Preferably, during the ball milling in step (3), the mass ratio of ball stone, mixed material and water is 2-3:1:0.4-0.6, and the ball milling time is 12-18 hours; after ball milling, the mixture is sieved through a 60-100 mesh sieve.

[0022] Preferably, the glaze dipping time in step (4) is 3 to 5 seconds, and the dipping is performed 2 to 3 times.

[0023] Preferably, the drying temperature in step (5) is 50-70° C., and the drying time is 2-4 hours.

[0024] Preferably, the high temperature sintering method in step (6) is: firstly raising the temperature from room temperature to 550-570°C within 200-220 minutes; then continuing to raise the temperature to 890-910°C within 110-130 minutes, and then continuing to raise the temperature to 1230-1250°C within 200-220 minutes.

[0025] Therefore, the present invention has the following beneficial effects:

[0026] (1) By adding an appropriate amount of spinel-garnet type red-brown composite pigment to the traditional wood ash glaze components of wood ash and clay, the color of the wood ash glaze can be adjusted from the traditional green to brown, meeting the market demand for diversified glaze colors;

[0027] (2) The addition of spinel-garnet composite crystals can significantly improve the thermal expansion properties and strength of the amorphous wood ash glaze, prevent it from cracking, and expand the application of wood ash glaze ceramic products. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with specific implementation methods.

[0029] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0030] Overall embodiment:

[0031] A brown wood ash glaze comprises the following raw materials, measured in parts by weight: 55-65 parts of wood ash, 30-40 parts of clay, and 3-8 parts of spinel-garnet type reddish brown composite pigment; the spinel-garnet type reddish brown composite pigment is prepared by co-firing 90-100 parts of FeCrZn spinel pigment, 13-15 parts of Y2O3, and 12-14 parts of Al2O3; the raw materials of the FeCrZn spinel pigment comprise, measured in parts by weight: 25-35 parts of Fe2O3, 15-20 parts of Cr2O3, and 35-55 parts of ZnO.

[0032] As a preferred solution, the clay components are as follows, in mass percentage: Na2O 0.05-0.07%, MgO 0.1-0.2%, Al2O3 18-19%, SiO2 74-76%, K2O 3-4%, CaO 0.1-0.2%, TiO2 0.08-0.12%, Fe2O3 0.7-0.9%, and the remainder is loss on ignition.

[0033] The method for preparing the above-mentioned brown plant ash glaze comprises the following steps:

[0034] (1) Pretreatment of wood ash and clay;

[0035] (2) Preparing a spinel-garnet type reddish brown composite pigment: Fe2O3, Cr2O3 and ZnO are mixed in proportion, pressed into shape, sintered and crushed to obtain a FeCrZn spinel pigment; then the FeCrZn spinel pigment is mixed with Y2O3 and Al2O3 in proportion, pressed into shape, sintered and crushed to obtain a spinel-garnet type reddish brown composite pigment;

[0036] (3) Mixing and ball milling: the pre-treated plant ash and clay are mixed with the spinel-garnet type red-brown composite pigment in proportion, and then the mixture is ball milled with water. After ball milling, the mixture is sieved to obtain a glaze;

[0037] (4) Glazing: placing the fired ceramic body into the glaze;

[0038] (5) Drying: Drying the ceramic body after glazing;

[0039] (6) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface.

[0040] As a preferred solution, during the pretreatment in step (1), the plant ash is passed through an 80-120 mesh sieve to remove impurities, then soaked in water for precipitation, the water is poured out after precipitation, new water is added, the precipitation is repeated 3-5 times, the water is poured out, and the pretreated plant ash is obtained after drying; when the clay is pretreated, the clay is crushed and passed through a 100-120 mesh sieve to remove impurities, thereby obtaining the pretreated clay.

[0041] As a preferred solution, when preparing FeCrZn spinel pigment in step (2), the sintering temperature is 1300-1400°C and the sintering time is 3-5 hours; when preparing spinel-garnet type reddish brown composite pigment, the sintering temperature is 1700-1750°C and the sintering time is 3-4 hours.

[0042] As a preferred solution, when preparing FeCrZn spinel pigment and spinel-garnet type reddish brown composite pigment in step (2), the pressed green body is dried at 100-120° C. for 12-24 h before sintering.

[0043] As a preferred solution, during the ball milling in step (3), the mass ratio of ball stone, mixed material and water is 2-3:1:0.4-0.6, and the ball milling time is 12-18 hours; after ball milling, the mixture is sieved through a 60-100 mesh sieve.

[0044] As a preferred solution, the glaze dipping time in step (4) is 3 to 5 seconds, and the dipping is performed 2 to 3 times.

[0045] As a preferred solution, the drying temperature in step (5) is 50-70° C. and the drying time is 2-4 hours.

[0046] As a preferred solution, the high temperature sintering method in step (6) is: firstly raise the temperature from room temperature to 550-570°C within 200-220 minutes; then continue to raise the temperature to 890-910°C within 110-130 minutes, and then continue to raise the temperature to 1230-1250°C within 200-220 minutes.

[0047] Embodiment 1:

[0048] A method for preparing a brown plant ash glaze comprises the following steps:

[0049] (1) Pretreatment of plant ash and clay: Commercially available plant ash was passed through a 100-mesh sieve to remove impurities, then soaked in water for precipitation, the water was poured out after precipitation, new water was added, the precipitation was repeated 5 times, the water was poured out, and the pretreated plant ash was obtained after drying; when pretreating clay, the clay (Wanjiawu mountain soil in Lin'an, Hangzhou) was crushed and passed through a 120-mesh sieve to remove impurities, thereby obtaining pretreated clay; the component contents of the clay were measured by the method in GB / T 4734-1996, and the mass percentages were: Na2O 0.06%, MgO 0.15%, Al2O3 18.84%, SiO2 75.11%, K2O 3.82%, CaO 0.13%, TiO2 0.10%, Fe2O3 0.81%, and the remainder was loss on ignition;

[0050] (2) Preparation of spinel-garnet type reddish brown composite pigment:

[0051] ① In parts by weight, 30 parts of Fe2O3, 18 parts of Cr2O3 and 45 parts of ZnO are mixed, pressed and formed, and the green body is dried at 110°C for 18 hours, and then sintered at 1350°C for 4 hours, and then crushed to obtain FeCrZn spinel pigment;

[0052] ② In parts by weight, 95 parts of FeCrZn spinel pigment are mixed with 14 parts of Y2O3 and 13 parts of α-Al2O3, and after pressing and molding, the green body is dried at 110°C for 18 hours, and then sintered at 1730°C for 3.5 hours, and then crushed to obtain a spinel-garnet type red-brown composite pigment;

[0053] (3) Mixed ball milling: 60 parts by weight of pretreated plant ash, 35 parts of pretreated clay and 5 parts of spinel-garnet type red-brown composite pigment were mixed evenly, and then the mixture was ball milled with water. During ball milling, the mass ratio of ball stone, mixture and water was 2.5:1:0.5, and the ball milling time was 16 hours. After ball milling, the glaze was passed through an 80-mesh sieve to obtain a glaze.

[0054] (4) bisque firing of a ceramic body: 65 parts of pretreated clay, 35 parts of kaolin and 3 parts of iron oxide were mixed by weight, and water was added to seal and aged for 4 months to obtain a mud material; the mud material was molded to obtain a ceramic body, and the ceramic body was bisque fired by heating from room temperature to 560° C. for 420 minutes, and then further heating to 700° C. for 90 minutes, and then cooled to room temperature to obtain a bisque fired ceramic body;

[0055] (5) Glaze dipping: Place the unglazed ceramic body into the glaze for 3 seconds each time, and dip twice;

[0056] (6) Drying: Dry the glazed ceramic body at 60°C for 3 h;

[0057] (7) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface. The high temperature firing method is: first, it takes 210 minutes to heat the temperature from room temperature to 560°C; then, it takes 120 minutes to continue to heat the temperature to 900°C, and then it takes 210 minutes to continue to heat the temperature to 1230°C.

[0058] Embodiment 2:

[0059] A method for preparing a brown plant ash glaze comprises the following steps:

[0060] (1) Pretreatment of plant ash and clay: Commercially available plant ash was passed through a 100-mesh sieve to remove impurities, then soaked in water for precipitation, the water was poured out after precipitation, new water was added, the precipitation was repeated 5 times, the water was poured out, and the pretreated plant ash was obtained after drying; when pretreating clay, the clay (Wanjiawu mountain soil in Lin'an, Hangzhou) was crushed and passed through a 120-mesh sieve to remove impurities, thereby obtaining pretreated clay; the component contents of the clay were measured by the method in GB / T 4734-1996, and the mass percentages were: Na2O 0.06%, MgO 0.15%, Al2O3 18.84%, SiO2 75.11%, K2O 3.82%, CaO 0.13%, TiO2 0.10%, Fe2O3 0.81%, and the remainder was loss on ignition;

[0061] (2) Preparation of spinel-garnet type reddish brown composite pigment:

[0062] ① In parts by weight, 25 parts of Fe2O3, 15 parts of Cr2O3 and 35 parts of ZnO are mixed, pressed and formed, and the green body is dried at 110°C for 18 hours, and then sintered at 1300°C for 5 hours, and then crushed to obtain FeCrZn spinel pigment;

[0063] ② In parts by weight, 90 parts of FeCrZn spinel pigment are mixed with 13 parts of Y2O3 and 12 parts of α-Al2O3, and after pressing and molding, the green body is dried at 110°C for 18 hours, and then sintered at 1700°C for 4 hours, and then crushed to obtain a spinel-garnet type red-brown composite pigment;

[0064] (3) Mixed ball milling: 55 parts by weight of pretreated plant ash, 30 parts by weight of pretreated clay and 3 parts by weight of spinel-garnet type red-brown composite pigment were mixed evenly, and then the mixture was ball milled with water. During ball milling, the mass ratio of ball stone, mixture and water was 2:1:0.5, and the ball milling time was 18 hours. After ball milling, the mixture was sieved with 80 mesh to obtain a glaze.

[0065] (4) bisque firing of a ceramic body: 65 parts of pretreated clay, 35 parts of kaolin and 3 parts of iron oxide were mixed by weight, and water was added to seal and aged for 4 months to obtain a mud material; the mud material was molded to obtain a ceramic body, and the ceramic body was bisque fired by heating from room temperature to 560° C. for 420 minutes, and then further heating to 700° C. for 90 minutes, and then cooled to room temperature to obtain a bisque fired ceramic body;

[0066] (5) Glaze dipping: Place the unglazed ceramic body into the glaze for 3 seconds each time, and do this 3 times;

[0067] (6) Drying: Dry the glazed ceramic body at 70°C for 2 h;

[0068] (7) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface. The high temperature firing method is: first, it takes 200 minutes to raise the temperature from room temperature to 550°C; then, it takes 130 minutes to continue to raise the temperature to 910°C, and then it takes 200 minutes to continue to raise the temperature to 1250°C.

[0069] Embodiment 3:

[0070] A method for preparing a brown plant ash glaze comprises the following steps:

[0071] (1) Pretreatment of plant ash and clay: Commercially available plant ash was passed through a 100-mesh sieve to remove impurities, then soaked in water for precipitation, the water was poured out after precipitation, new water was added, the precipitation was repeated 5 times, the water was poured out, and the pretreated plant ash was obtained after drying; when pretreating clay, the clay (Wanjiawu mountain soil in Lin'an, Hangzhou) was crushed and passed through a 120-mesh sieve to remove impurities, thereby obtaining pretreated clay; the component contents of the clay were measured by the method in GB / T 4734-1996, and the mass percentages were: Na2O 0.06%, MgO 0.15%, Al2O3 18.84%, SiO2 75.11%, K2O 3.82%, CaO 0.13%, TiO2 0.10%, Fe2O3 0.81%, and the remainder was loss on ignition;

[0072] (2) Preparation of spinel-garnet type reddish brown composite pigment:

[0073] ① In parts by weight, 35 parts of Fe2O3, 20 parts of Cr2O3 and 55 parts of ZnO are mixed, pressed and formed, and the green body is dried at 120°C for 12 hours, and then sintered at 1400°C for 3 hours, and then crushed to obtain FeCrZn spinel pigment;

[0074] ② In parts by weight, 100 parts of FeCrZn spinel pigment are mixed with 15 parts of Y2O3 and 14 parts of α-Al2O3, and after pressing and molding, the green body is dried at 100°C for 24 hours, and then sintered at 1750°C for 3 hours, and then crushed to obtain a spinel-garnet type red-brown composite pigment;

[0075] (3) Mixed ball milling: 65 parts by weight of pretreated plant ash, 40 parts by weight of pretreated clay and 8 parts by weight of spinel-garnet type red-brown composite pigment were mixed evenly, and then the mixture was ball milled with water. During ball milling, the mass ratio of ball stone, mixture and water was 3:1:0.5, and the ball milling time was 12 h. After ball milling, the mixture was sieved with 80 mesh to obtain a glaze.

[0076] (4) bisque firing of a ceramic body: 65 parts of pretreated clay, 35 parts of kaolin and 3 parts of iron oxide were mixed by weight, and water was added to seal and aged for 4 months to obtain a mud material; the mud material was molded to obtain a ceramic body, and the ceramic body was bisque fired by heating from room temperature to 560° C. for 420 minutes, and then further heating to 700° C. for 90 minutes, and then cooled to room temperature to obtain a bisque fired ceramic body;

[0077] (5) Glaze dipping: Place the unglazed ceramic body into the glaze for 5 seconds each time, and dip twice;

[0078] (6) Drying: Dry the glazed ceramic body at 50°C for 4 hours;

[0079] (7) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface. The high temperature firing method is: first, it takes 220 minutes to heat the temperature from room temperature to 570°C; then, it takes 110 minutes to continue to heat the temperature to 890°C, and then it takes 220 minutes to continue to heat the temperature to 1230°C.

[0080] Comparative Example 1 (without adding spinel-garnet type reddish brown composite pigment):

[0081] A method for preparing plant ash glaze comprises the following steps:

[0082] (1) Pretreatment of plant ash and clay: Commercially available plant ash was passed through a 100-mesh sieve to remove impurities, then soaked in water for precipitation, the water was poured out after precipitation, new water was added, the precipitation was repeated 5 times, the water was poured out, and the pretreated plant ash was obtained after drying; when pretreating clay, the clay (Wanjiawu mountain soil in Lin'an, Hangzhou) was crushed and passed through a 120-mesh sieve to remove impurities, thereby obtaining pretreated clay; the component contents of the clay were measured by the method in GB / T 4734-1996, and the mass percentages were: Na2O 0.06%, MgO 0.15%, Al2O3 18.84%, SiO2 75.11%, K2O 3.82%, CaO 0.13%, TiO2 0.10%, Fe2O3 0.81%, and the remainder was loss on ignition;

[0083] (2) Mixed ball milling: 60 parts by weight of pretreated plant ash and 35 parts by weight of pretreated clay were mixed evenly, and the mixture was ball milled with water. During ball milling, the mass ratio of ball stone, mixture and water was 2.5:1:0.5, and the ball milling time was 16 hours. After ball milling, the glaze was passed through an 80-mesh sieve to obtain a glaze.

[0084] (3) bisque firing of a ceramic body: 65 parts of pretreated clay, 35 parts of kaolin and 3 parts of iron oxide were mixed by weight, and water was added to seal and aged for 4 months to obtain a mud material; the mud material was molded to obtain a ceramic body, and the ceramic body was bisque fired by heating from room temperature to 560° C. for 420 min, and then further heating to 700° C. for 90 min, and then cooled to room temperature to obtain a bisque fired ceramic body;

[0085] (4) Glaze dipping: Place the unglazed ceramic body into the glaze for 3 seconds each time, and dip twice;

[0086] (5) Drying: Dry the glazed ceramic body at 60°C for 3 h;

[0087] (6) Firing: The dried ceramic body is fired at high temperature to obtain the wood ash glaze on the surface. The high temperature firing method is: first, it takes 210 minutes to heat the temperature from room temperature to 560°C; then, it takes 120 minutes to continue to heat the temperature to 900°C, and then, it takes 210 minutes to continue to heat the temperature to 1230°C.

[0088] Comparative Example 2 (using Fe2O3 as pigment):

[0089] A method for preparing a brown plant ash glaze comprises the following steps:

[0090] (1) Pretreatment of plant ash and clay: Commercially available plant ash was passed through a 100-mesh sieve to remove impurities, then soaked in water for precipitation, the water was poured out after precipitation, new water was added, the precipitation was repeated 5 times, the water was poured out, and the pretreated plant ash was obtained after drying; when pretreating clay, the clay (Wanjiawu mountain soil in Lin'an, Hangzhou) was crushed and passed through a 120-mesh sieve to remove impurities, thereby obtaining pretreated clay; the component contents of the clay were measured by the method in GB / T 4734-1996, and the mass percentages were: Na2O 0.06%, MgO 0.15%, Al2O3 18.84%, SiO2 75.11%, K2O 3.82%, CaO 0.13%, TiO2 0.10%, Fe2O3 0.81%, and the remainder was loss on ignition;

[0091] (2) Mixed ball milling: 60 parts by weight of pretreated plant ash, 35 parts of pretreated clay and 5 parts of Fe2O3 were mixed evenly and then the mixture was ball milled with water. During ball milling, the mass ratio of ball stone, mixture and water was 2.5:1:0.5, and the ball milling time was 16 hours. After ball milling, the glaze was passed through an 80-mesh sieve to obtain a glaze.

[0092] (3) bisque firing of a ceramic body: 65 parts of pretreated clay, 35 parts of kaolin and 3 parts of iron oxide were mixed by weight, and water was added to seal and aged for 4 months to obtain a mud material; the mud material was molded to obtain a ceramic body, and the ceramic body was bisque fired by heating from room temperature to 560° C. for 420 min, and then further heating to 700° C. for 90 min, and then cooled to room temperature to obtain a bisque fired ceramic body;

[0093] (4) Glaze dipping: Place the unglazed ceramic body into the glaze for 3 seconds each time, and dip twice;

[0094] (5) Drying: Dry the glazed ceramic body at 60°C for 3 h;

[0095] (6) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface. The high temperature firing method is: first, it takes 210 minutes to heat the temperature from room temperature to 560°C; then, it takes 120 minutes to continue to heat the temperature to 900°C; and then, it takes 210 minutes to continue to heat the temperature to 1230°C.

[0096] Comparative Example 3 (using only FeCrZn spinel as pigment):

[0097] A method for preparing a brown plant ash glaze comprises the following steps:

[0098] (1) Pretreatment of plant ash and clay: Commercially available plant ash was passed through a 100-mesh sieve to remove impurities, then soaked in water for precipitation, the water was poured out after precipitation, new water was added, the precipitation was repeated 5 times, the water was poured out, and the pretreated plant ash was obtained after drying; when pretreating clay, the clay (Wanjiawu mountain soil in Lin'an, Hangzhou) was crushed and passed through a 120-mesh sieve to remove impurities, thereby obtaining pretreated clay; the component contents of the clay were measured by the method in GB / T 4734-1996, and the mass percentages were: Na2O 0.06%, MgO 0.15%, Al2O3 18.84%, SiO2 75.11%, K2O 3.82%, CaO 0.13%, TiO2 0.10%, Fe2O3 0.81%, and the remainder was loss on ignition;

[0099] (2) Preparation of spinel red-brown pigment: 30 parts by weight of Fe2O3, 18 parts of Cr2O3 and 45 parts of ZnO were mixed, pressed and molded, and the green body was dried at 110°C for 18 hours, then sintered at 1350°C for 4 hours, and crushed to obtain FeCrZn spinel pigment;

[0100] (3) Mixed ball milling: 60 parts by weight of pretreated wood ash, 35 parts of pretreated clay and 5 parts of FeCrZn spinel pigment were mixed evenly, and then the mixture was ball milled with water. During ball milling, the mass ratio of spinel, mixture and water was 2.5:1:0.5, and the ball milling time was 16 hours. After ball milling, the glaze was passed through an 80-mesh sieve to obtain a glaze.

[0101] (4) bisque firing of a ceramic body: 65 parts of pretreated clay, 35 parts of kaolin and 3 parts of iron oxide were mixed by weight, and water was added to seal and aged for 4 months to obtain a mud material; the mud material was molded to obtain a ceramic body, and the ceramic body was bisque fired by heating from room temperature to 560° C. for 420 minutes, and then further heating to 700° C. for 90 minutes, and then cooled to room temperature to obtain a bisque fired ceramic body;

[0102] (5) Glaze dipping: Place the unglazed ceramic body into the glaze for 3 seconds each time, and dip twice;

[0103] (6) Drying: Dry the glazed ceramic body at 60°C for 3 h;

[0104] (7) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface. The high temperature firing method is: first, it takes 210 minutes to heat the temperature from room temperature to 560°C; then, it takes 120 minutes to continue to heat the temperature to 900°C, and then it takes 210 minutes to continue to heat the temperature to 1230°C.

[0105] Comparative Example 4 (direct sintering of spinel and garnet):

[0106] A method for preparing a brown plant ash glaze comprises the following steps:

[0107] (1) Pretreatment of plant ash and clay: Commercially available plant ash was passed through a 100-mesh sieve to remove impurities, then soaked in water for precipitation, the water was poured out after precipitation, new water was added, the precipitation was repeated 5 times, the water was poured out, and the pretreated plant ash was obtained after drying; when pretreating clay, the clay (Wanjiawu mountain soil in Lin'an, Hangzhou) was crushed and passed through a 120-mesh sieve to remove impurities, thereby obtaining pretreated clay; the component contents of the clay were measured by the method in GB / T 4734-1996, and the mass percentages were: Na2O 0.06%, MgO 0.15%, Al2O3 18.84%, SiO2 75.11%, K2O 3.82%, CaO 0.13%, TiO2 0.10%, Fe2O3 0.81%, and the remainder was loss on ignition;

[0108] (2) Preparation of spinel-garnet type reddish brown composite pigment:

[0109] ① In parts by weight, 30 parts of Fe2O3, 18 parts of Cr2O3 and 45 parts of ZnO are mixed, pressed and formed, and the green body is dried at 110°C for 18 hours, and then sintered at 1350°C for 4 hours, and then crushed to obtain FeCrZn spinel pigment;

[0110] ② Mix 95 parts of FeCrZn spinel pigment with 27 parts of commercially available yttrium aluminum garnet (YAG) powder, press and mold the green body, dry it at 110°C for 18 hours, then sinter it at 1730°C for 3.5 hours, and crush it to obtain a spinel-garnet type red-brown composite pigment;

[0111] (3) Mixed ball milling: 60 parts by weight of pretreated plant ash, 35 parts of pretreated clay and 5 parts of spinel-garnet type red-brown composite pigment were mixed evenly, and then the mixture was ball milled with water. During ball milling, the mass ratio of ball stone, mixture and water was 2.5:1:0.5, and the ball milling time was 16 hours. After ball milling, the glaze was passed through an 80-mesh sieve to obtain a glaze.

[0112] (4) bisque firing of a ceramic body: 65 parts of pretreated clay, 35 parts of kaolin and 3 parts of iron oxide were mixed by weight, and water was added to seal and aged for 4 months to obtain a mud material; the mud material was molded to obtain a ceramic body, and the ceramic body was bisque fired by heating from room temperature to 560° C. for 420 minutes, and then further heating to 700° C. for 90 minutes, and then cooled to room temperature to obtain a bisque fired ceramic body;

[0113] (5) Glaze dipping: Place the unglazed ceramic body into the glaze for 3 seconds each time, and dip twice;

[0114] (6) Drying: Dry the glazed ceramic body at 60°C for 3 h;

[0115] (7) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface. The high temperature firing method is: first, it takes 210 minutes to heat the temperature from room temperature to 560°C; then, it takes 120 minutes to continue to heat the temperature to 900°C, and then it takes 210 minutes to continue to heat the temperature to 1230°C.

[0116] The properties of the wood ash glazes prepared in the above examples and comparative examples were tested, and the results are shown in Table 1.

[0117] The high temperature resistance test method is as follows: put the ceramic product sample into an oven preheated to 150℃±2℃ higher than the cold water temperature, make the sample temperature reach the preheating temperature within 5 minutes, start timing, and keep at this temperature for 45 minutes; take out the sample and immediately immerse it in a water tank filled with running cold water, cool it for 5 minutes, this is a hot and cold cycle; after 5 cycles, check and record the damage of each sample during the rapid cooling and heating process;

[0118] The test method for modulus of rupture refers to GB / T3810.4-2016.

[0119] Table 1: Test results of wood ash glaze performance.

[0120]

[0121] As can be seen from Table 1, in Examples 1 to 3, the method of the present invention is adopted to add a spinel-garnet type red-brown composite pigment to the plant ash glaze. Compared with the traditional plant ash glaze without adding a pigment in Comparative Example 1, the glaze color can be adjusted from blue-gray to brown, which can meet the market demand for diversified glaze colors. At the same time, after adding the spinel-garnet type red-brown composite pigment of the present invention, the thermal expansion coefficient of the glaze is significantly reduced compared with that of Comparative Example 1, and the high temperature resistance and the modulus of rupture are also significantly improved, which can avoid the cracking of the plant ash glaze and extend the service life of the ceramic product.

[0122] In Comparative Example 2, iron oxide is used instead of the spinel-garnet reddish-brown composite pigment in the present invention. Although the glaze color can be adjusted to a brown color, the thermal expansion coefficient, high temperature resistance and rupture modulus of the glaze are significantly reduced compared with those in Example 1, which is not conducive to improving the service life of ceramic products.

[0123] In Comparative Example 3, only FeCrZn spinel is used as a pigment, and it is not co-fired with Y2O3 and Al2O3. Due to the lack of the compounding of yttrium aluminum garnet, the various properties of the glaze are reduced compared with those in Example 1; in Comparative Example 4, FeCrZn spinel and yttrium aluminum garnet are directly co-fired instead of co-fired with Y2O3 and Al2O3, and the various properties of the glaze are also reduced compared with those in Example 1, indicating that the solid solution formed when FeCrZn spinel and Al2O3 are co-fired is beneficial to improving the performance of the glaze.

[0124] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A sauce-colored plant ash glaze, characterized in that: The raw materials include the following in parts by weight: 55-65 parts of plant ash, 30-40 parts of clay, and 3-8 parts of spinel-garnet type reddish brown composite pigment; The spinel-garnet type reddish brown composite pigment is prepared by co-firing 90-100 parts of FeCrZn spinel pigment, 13-15 parts of Y2O3 and 12-14 parts of Al2O3; the raw materials of the FeCrZn spinel pigment include, by weight, 25-35 parts of Fe2O3, 15-20 parts of Cr2O3 and 35-55 parts of ZnO.

2. The brown wood ash glaze according to claim 1, characterized in that: Calculated in mass percentage, the clay components are as follows: Na2O 0.05-0.07%, MgO 0.1-0.2%, Al2O3 18-19%, SiO2 74-76%, K2O 3-4%, CaO 0.1-0.2%, TiO2 0.08-0.12%, Fe2O3 0.7-0.9%, and the remainder is the loss on ignition.

3. A method for preparing the brown wood ash glaze as claimed in claim 1 or 2, characterized in that: The steps include: (1) Pretreatment of wood ash and clay; (2) Preparation of spinel-garnet type red-brown composite pigment: Fe2O3, Cr2O3 and ZnO are mixed in proportion, pressed into shape, sintered and crushed to obtain FeCrZn spinel pigment; FeCrZn spinel pigment is then mixed with Y2O3 and Al2O3 in proportion, pressed into shape, sintered and crushed to obtain spinel-garnet type red-brown composite pigment; (3) Mixed ball milling: The pretreated plant ash and clay are mixed with the spinel-garnet type red-brown composite pigment in a certain proportion, and then the mixture is ball milled with water. After ball milling, the mixture is sieved to obtain a glaze; (4) Glaze dipping: Place the fired ceramic body into the glaze for dipping; (5) Drying: Drying the ceramic body after glazing; (6) Firing: The dried ceramic body is fired at high temperature to obtain the brown wood ash glaze on the surface.

4. The preparation method according to claim 3, characterized in that: In the pretreatment in step (1), the plant ash is passed through an 80-120 mesh sieve to remove impurities, then soaked in water for precipitation, the water is poured out after precipitation, new water is added, the precipitation is repeated 3-5 times, the water is poured out, and the pretreated plant ash is obtained after drying; when the clay is pretreated, the clay is crushed and passed through a 100-120 mesh sieve to remove impurities, thereby obtaining the pretreated clay.

5. The preparation method according to claim 3, characterized in that: When preparing FeCrZn spinel pigment in step (2), the sintering temperature is 1300-1400°C and the sintering time is 3-5 hours; when preparing spinel-garnet type reddish brown composite pigment, the sintering temperature is 1700-1750°C and the sintering time is 3-4 hours.

6. The preparation method according to claim 3 or 5, characterized in that: When preparing the FeCrZn spinel pigment and the spinel-garnet type reddish brown composite pigment in step (2), the pressed green body is dried at 100-120° C. for 12-24 h before sintering.

7. The preparation method according to claim 3, characterized in that: During the ball milling in step (3), the mass ratio of ball stone, mixed material and water is 2-3:1:0.4-0.6, and the ball milling time is 12-18 hours; after ball milling, the mixture is sieved through a 60-100 mesh sieve.

8. The preparation method according to claim 3, characterized in that: In step (4), the glaze dipping time is 3 to 5 seconds, and the dipping is performed 2 to 3 times.

9. The preparation method according to claim 3, characterized in that: The drying temperature in step (5) is 50-70°C and the drying time is 2-4 hours.

10. The preparation method according to claim 3, characterized in that: The high temperature firing method in step (6) is: firstly, the temperature is raised from room temperature to 550-570°C within 200-220 minutes; then, the temperature is further raised to 890-910°C within 110-130 minutes, and then, the temperature is further raised to 1230-1250°C within 200-220 minutes.

Citation Information

Patent Citations

  • Caramel clay pottery preparation method

    CN105294069A

  • Low-temperature corrosion-resistant glaze material used for enamel pipe

    CN105948495A